Understanding the Outstanding High‐Voltage Performance of NCM523||Graphite Lithium Ion Cells after Elimination of Ethylene Carbonate Solvent from Conventional Electrolyte. Issue 14 (29th January 2021) - Klein, Sven; van Wickeren, Stefan; Röser, Stephan; Bärmann, Peer; Borzutzki, Kristina; Heidrich, Bastian; Börner, Markus; Winter, Martin; Placke, Tobias; Kasnatscheew, Johannes
Abstract: The increase of specific energy of current Li ion batteries via further increase of the cell voltage, for example, to 4.5 V is typically accompanied by a sudden and rapid capacity fade, known as "rollover" failure. This failure is the result of Li dendrite formation triggered in the course of electrode cross‐talk, that is, dissolution of transition metals (TMs) from the cathode and deposition on the anode. It is shown herein, that the elimination of ethylene carbonate (EC) from a state‐of‐the‐art electrolyte, that is, from 1.0 m LiPF6 in a 3:7 mixture of EC and ethyl methyl carbonate prevents this failure in high‐voltage LiNi0.5 Co0.2 Mn0.3 O2 ||graphite cells, even without any electrolyte additives. While the oxidative stability on the cathode side is similar in both electrolytes, visible by a decomposition plateau at 5.5 V versus Li|Li + during charge, the anode side in the EC‐free electrolyte reveals significantly less TM deposits and Li metal dendrites compared to the EC‐based electrolyte. The beneficial effect of EC‐free electrolytes is related to a significantly increased amount of degraded LiPF6 species, which effectively trap dissolved TMs and suppress the effect of detrimental cross‐talk, finally realizing rollover‐free performance under high voltage conditions. Abstract : It is shown that elimination of ethylene carbonate (EC) from conventional electrolytes has a beneficial impact on cycle life in high voltage Li ion batteries, e.g. with LiNi0.5 Co0.2 Mn0.3 O2 cathodes. The significantly enhanced decomposition products of LiPF6 in EC‐free electrolytes effectively bond dissolved transition metals, originating from electrode crosstalk, and can suppress even the rollover failure.